2021
DOI: 10.3390/ijerph18199962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tadalafil Administration on Redox Homeostasis and Polyamine Levels in Healthy Men with High Level of Physical Activity

Abstract: Background: The phosphodiesterase type 5 inhibitor (PDE5I) tadalafil, in addition to its therapeutic role, has shown antioxidant effects in different in vivo models. Supplementation with antioxidants has received interest as a suitable tool for preventing or reducing exercise-related oxidative stress, possibly leading to the improvement of sport performance in athletes. However, the use/abuse of these substances must be evaluated not only within the context of amateur sport, but especially in competitions wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…As oxidation of the fatty acids needs more oxygen than glucose oxidation, elevated oxygen consumption in mitochondrial increases formation of the ROS (Zhang et al, 2021). Glutathione is the primary antioxidant responsible for maintaining a reduced intracellular microenvironment, and Tadalafil administration produced a redox perturbation by the altered GSH/GSSG ratio with no effect on TAS (Duranti, Ceci, et al, 2021; Duranti, Maldini, et al, 2021) which our findings were in agreement to this report. It is assumed that increase in cGMP, directly or indirectly, may lead to modify enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As oxidation of the fatty acids needs more oxygen than glucose oxidation, elevated oxygen consumption in mitochondrial increases formation of the ROS (Zhang et al, 2021). Glutathione is the primary antioxidant responsible for maintaining a reduced intracellular microenvironment, and Tadalafil administration produced a redox perturbation by the altered GSH/GSSG ratio with no effect on TAS (Duranti, Ceci, et al, 2021; Duranti, Maldini, et al, 2021) which our findings were in agreement to this report. It is assumed that increase in cGMP, directly or indirectly, may lead to modify enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
“…CAT activity decreased during the development of rodent brain, and administration of the Tadalafil increased CAT levels (Al‐Amin et al, 2014). In this regard, Duranti, Ceci, et al (2021) and Duranti, Maldini, et al (2021) demonstrate that Tadalafil improved oxidative capacity in C2C12 skeletal muscle cells by enhancing fat metabolism. As oxidation of the fatty acids needs more oxygen than glucose oxidation, elevated oxygen consumption in mitochondrial increases formation of the ROS (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, our laboratory, along with others, has demonstrated that PDE5i, including tadalafil, may modulate muscle metabolism and response to ROS under physiological and pathological conditions, in either in vitro or in vivo studies [ 27 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 myoblasts Trolox ® equivalents antioxidant capacity was evaluated spectrophotometrically, as previously described [ 76 , 77 ]. This assay evaluates the ability of cell lysates in preventing ABTS+ radical formation, compared to Trolox ® (vitamin E analogue) standards.…”
Section: Methodsmentioning
confidence: 99%